2014
DOI: 10.1242/jeb.101584
|View full text |Cite
|
Sign up to set email alerts
|

Defensive slime formation in Pacific hagfish requires Ca2+ and aquaporin mediated swelling of released mucin vesicles

Abstract: Hagfishes defend themselves from fish predators via the rapid deployment of a fibrous slime that adheres to and clogs gills. The slime transforms from a thick glandular exudate to a fully hydrated product in a fraction of a second through a process that involves the swelling and rupture of numerous mucin vesicles. Here we demonstrate that the vesicle membrane plays an important role in regulating the swelling of mucin granules, and provide evidence that the membrane contains proteins that facilitate the moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 58 publications
0
37
1
Order By: Relevance
“…10.1021/acs.biomac.5b00552 Biomacromolecules XXXX, XXX, XXX−XXX B the assembly, structure, functional mechanics, and evolution of the keratin gene/protein family.…”
mentioning
confidence: 99%
“…10.1021/acs.biomac.5b00552 Biomacromolecules XXXX, XXX, XXX−XXX B the assembly, structure, functional mechanics, and evolution of the keratin gene/protein family.…”
mentioning
confidence: 99%
“…Although it is known that flow is required to accelerate unravelling to t dep,50% , 1 s, it is not yet clear whether flow-enhanced ion transport may also contribute to a faster unravelling, in addition to the drag effects. The effects of various salt ions on the swelling and rupture of mucin vesciles have been studied in the past [18,19], but the influence of such ionic effects on the skeins and their deployment is not yet known. If ion transport and chemistry are important, this would modify the F P behaviour and require royalsocietypublishing.org/journal/rsif J. R. Soc.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic stepwise changes of AQP4 palmitoylation motifs in vertebrate evolution As described above, sequence analysis of total 224 vertebrate species from primitive hagfishes [23] to human showed that the palmitoylation sites are almost completely conserved with limited exceptions (Table 1). Cyclostomes consist of hagfishes and lampreys, which are the primitive jawless vertebrates belonging to the superclasss Agnatha.…”
Section: Acquisition and Complete Conservation Of Palmitoylation Sitementioning
confidence: 87%